2021
DOI: 10.3390/jpm11090864
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Exudative Pleural Effusions Based on Pleural Adenosine Deaminase (ADA)-C-Reactive Protein (CRP) Levels, and Their Combination: An Observational Prospective Study

Abstract: (1) Background: Malignant (MPE), parapneumonic (PPE) and tuberculous (TPE) pleural effusions constitute common causes of pleurisy. Discriminating among them is usually challenging. C-reactive protein (CRP) and adenosine deaminase (ADA) pleural levels (p-CRP, p-ADA) have been used as differentiators in many studies showing promising results. This study aims to evaluate the diagnostic value of p-CRP, p-ADA levels and their combination among the three categories. (2) Methods: A prospective study of 100 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Pleural exudative e usion (PEE) is the most common one in pleural e usion, and it is mainly caused by benign lesions such as tuberculosis, in ammation, and connective tissue disease, as well as malignant tumors such as lung cancer, pleural mesothelioma and metastatic tumor. According to the di erent properties of PEE, it can be divided into benign PEE and malignant PEE [1,2]. At present, the identi cation of benign and malignant PEE is mainly through medical history, pleural e usion examination, pleural biopsy, and exfoliated cytology culture in the thoracic cavity [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Pleural exudative e usion (PEE) is the most common one in pleural e usion, and it is mainly caused by benign lesions such as tuberculosis, in ammation, and connective tissue disease, as well as malignant tumors such as lung cancer, pleural mesothelioma and metastatic tumor. According to the di erent properties of PEE, it can be divided into benign PEE and malignant PEE [1,2]. At present, the identi cation of benign and malignant PEE is mainly through medical history, pleural e usion examination, pleural biopsy, and exfoliated cytology culture in the thoracic cavity [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Poor clinical outcomes and increased mortality can be associated with the development of parapneumonic effusions [ 20 ]. Research shows that hypoalbuminaemia, hyponatraemia and an elevated CRP have been identified as independent risk factors for mortality [ 8 , 21 ]. In this study, a retrospective analysis of the clinical data of 132 elderly patients with CAP in our hospital showed that the proportion of elderly patients with CAP combined with PPE was 40.9%, and the in-hospital mortality of pneumonia patients with PPE was significantly higher than those of patients with pneumonia alone.…”
Section: Discussionmentioning
confidence: 99%